2000
DOI: 10.1016/s0378-1097(00)00289-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a gene region involved in lipopolysaccharide biosynthesis in Bradyrhizobium japonicum: cloning, sequencing and expression of rfaf gene

Abstract: A 3.0-kb region involved in lipopolysaccharide biosynthesis in Bradyrhizobium japonicum was sequenced. One complete open reading frame was identified which encodes a polypeptide of 354 amino acid residues with a predicted molecular mass of 38 209 Da. Expression of the protein using a T7 gene expression system revealed a band of similar molecular mass after sodium dodecyl sulfate^polyacrylamide gel electrophoresis. A database search against known gene sequences revealed a significant sequence similarity to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The genes relating to bacterial surface polysaccharides, such as putative lipopolysaccharide (LPS) biosynthesis genes (rfaD, rfaE, and rfaF) (35,71), putative exopolysaccharide biosynthesis genes (expE5) (8,29), and putative K antigen biosynthesis genes (rkpA) (43) were also identified. These polysaccharides are important in symbiosis, either as structural components or as signaling molecules (58,72).…”
Section: Discussionmentioning
confidence: 99%
“…The genes relating to bacterial surface polysaccharides, such as putative lipopolysaccharide (LPS) biosynthesis genes (rfaD, rfaE, and rfaF) (35,71), putative exopolysaccharide biosynthesis genes (expE5) (8,29), and putative K antigen biosynthesis genes (rkpA) (43) were also identified. These polysaccharides are important in symbiosis, either as structural components or as signaling molecules (58,72).…”
Section: Discussionmentioning
confidence: 99%
“…To restore the function of lpcC in the mutant, a complementary strain was constructed by inserting a 2·2‐kb BamHI/PstI‐restricted fragment containing lpcC , derived from pLps (So et al . ), into pLAFR3 (Staskawicz et al . ), resulting in pCS7.…”
Section: Methodsmentioning
confidence: 99%
“…The Tn5‐inserted 5·5‐kb nucleotide fragment involved in LPS biosynthesis was subsequently cloned (So ), and within the cloned region, three open reading frames (ORFs) including rfaF (So et al . ), rfaD (Noh et al . ) and galE (Chang et al .…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we identified a gene region involved in lipopolysaccharide synthesis in B. japonicum 61A101C using Tn5 mutagenesis (Stacey et al , 1991). Subsequently, nucleotide sequence analysis of the region revealed the presence of rfaF and rfaD encoding heptosyltransferase and heptose epimerase, respectively (So, 1991; So et al , 2000; Noh et al , 2002). Here, we extend our knowledge of B. japonicum lipopolysaccharide by characterizing another ORF, designated galE based on its sequence similarity with that of other bacteria, specifically rhizobia and its ability to complement an Escherichia coli galE mutant.…”
Section: Introductionmentioning
confidence: 99%